THE EFFECTS OF PARTNERSHIP AND ENTREPRENEURSHIP TOWARD BUSINESS PERFORMANCE OF OYSTER MUSHROOM (PLEUROTUSOSTREATUS) - Edi Sucipto; Rina Oktaviani; Rizal Rizal (School of Business, IPB University (SB-IPB), 2015)
This study aimed to 1) analyze the effect of power on the performance of oyster mushroom business in Jember; 2) analyze the effect of partnerships on the performance of the white oyster mushroom business in Jember; and 3) analyze the effect of entrepreneurship on the performance of oyster mushroom business in Jember. The population in this study included the oyster mushroom cultivation farmers in Jember with the total population of 144 farmers; however, this study only used a sample size of 114 people. The data analysis method used was SEM (Structural Equation Modeling). Based on the analysis of data, it can be concluded that the power and partnerships have a significant effect, whereas entrepreneurship does not have a significant effect on the performance of oyster mushroom businesses in Jember. The study has managerial implications for the policy makers with the approach of: 1) prioritizing the power of the company that has a social characteristic by providing benefits in the form of non-materials, and this must be consistently implemented; 2) increasing partnership strategy through regular supervisions; 3) setting aside any entrepreneurial spirit which can jeorpardize the decision making in increasing production when prices are low.Keywords: power, partnership, entrepreneurship, business performanceABSTRAKPenelitian ini bertujuan 1) menganalisis pengaruh kekuasaan terhadap kinerja bisnis jamur tiram putih di Kabupaten Jember; 2) menganalisis pengaruh kemitraan terhadap kinerja bisnis jamur tiram putih di Kabupaten Jember; dan 3) menganalisis pengaruh kewirausahaan terhadap kinerja bisnis jamur tiram putih di Kabupaten Jember. Populasi dalam penelitian ini adalah petani budidaya jamur tiram putih di Kabupaten Jember. Jumlah populasi sebanyak 144 Petani budidaya jamur tiram putih. Penelitian ini menggunakan ukuran sampel dari 114 orang. Metode analisis data yang digunakan SEM (Structural Equation Modeling). Berdasarkan hasil analisis data maka dapat disimpulkan bahwa kekuasaan dan kemitraan berpengaruh signifikan, sedangkan kewirausahaan tidak berpengaruh signifikan terhadap kinerja bisnis jamur tiram putih di Kabupaten Jember. Penelitian memiliki implikasi manajerial bagi pengambil kebijakan melalui pendekatan: 1) Memprioritaskan kekuasaan perusahaan yang bersifat sosial melalui memberikan imbalan berupa in-materiil yaitu konsisten dalam berkomitmen; 3) Peningkatan strategi pola kemitraan melalui pengawasan secara rutin; 4) Mengesampingkan jiwa kewirausahaan yang beresiko dalam memutuskan peningkatan produksi saat harga rendah.Kata kunci: kekuasaan, kemitraan, kewirausahaan, kinerja bisnis